Optimal operation of shared energy storage-assisted wind–solar–thermal power generation systems under the electricity-carbon markets - Song, Xiaoling; Wu, Han; Zhang, Jiale; Zhao, Chuandang; Peña-Mora, Feniosky (Energy (Oxford), 2025)
The goal of sustainable development has led to significant advancements in renewable energy. The intermittent nature of wind and solar energy requires the flexible incorporation of thermal power generators and energy storage systems. A major obstacle to the widespread adoption of energy storage is the high initial investment, while thermal generators continue to be a significant source of carbon dioxide emissions, leading to environmental concerns. To address these issues, the energy storage sharing and carbon emission trading mechanisms are often utilized as effective strategies. Nonetheless, the operation of wind–solar–thermal power generation systems that utilize shared energy storage in coordinated electricity and carbon markets requires further research. Moreover, the existing methods overlook the importance of investigating how energy storage sharing and carbon trading mechanisms impact low-carbon and economic performances. Therefore, this paper develops a mixed-integer nonlinear model designed to optimize the day-ahead operational strategy for a hybrid power generation system, focusing on balancing economic and low-carbon objectives in the context of coordinated electricity and carbon markets. The model takes into account the operational dynamics of shared energy storage systems across different renewable energy generation facilities to facilitate the integration of clean energy sources. Four operational scenarios are proposed to evaluate the synergistic effects of energy storage sharing and carbon trading mechanisms on enhancing renewable energy utilization rate. The findings reveal that the hybrid system operator can achieve at least a 9.95% reduction in power generation costs compared to a baseline scenario that does not include the energy sharing model or the carbon trading market. Furthermore, the utilization rates of wind and solar energy increases to 97.43%. The implementation of the carbon trading market is also shown to play a crucial role in significantly reducing carbon dioxide emissions, resulting in a 6.99% decrease in carbon dioxide emission costs for the system operator. •A wind–solar–thermal power generation system that incorporates shared energy storage is introduced.•Integrating energy storage sharing and carbon trading mechanisms can increase economic benefits and lower carbon emissions.•The utilization rates of wind and solar energy increases to 97.43%.•The economic performance is most significantly influenced by the coefficients of CCER and the free carbon quota.